Pediatric Acute Lymphoblastic Leukemia With Hypereosinophilia and IDH2 Gene Mutation: A Case Report and Literature Review. Issue 2 (29th March 2022) - Gho, Deborah S.; Cooper, Robert M.
Abstract : Eosinophilia is a rare presentation of acute lymphoblastic leukemia (ALL) within the pediatric population. In this report, we present a patient with pre-B ALL and eosinophilia in the setting of an isocitrate dehydrogenase-2 gene mutation. These mutations have been described in patients with acute myeloid leukemia but in very few patients with ALL.